Determinan Penyaluran Kredit UMKM PT. Bank Maluku Malut - Jacobs, Sammie; Hukom, Maximiliane Cornelia Leonora (Public Policy, 2020)
Analysis of the influence factor- factor which influence channeling credit MSME Development Bank Regional Maluku- Malut shows the results of the positive and reassuring . In the concrete effects of the positive it means that the Bank with establishment Regional Maluku , North Maluku has shown its role as an institution of banking which are not directly able to influence regional economic growth . Assessment of the influence factor- factor distribution of credit SMEs in Regional Development Bank Maluku , North Maluku are quantitative already done by using the approach of the model test assumptions of classical and equation regression multiple . Once through the various stages of testing in the statistics , the model indicates that the variable CAR (X1) variable NPL (X2) and variable ROA (X3) is able to influence the distribution of credit SMEs in Regional Development Bank Maluku, North Maluku and is directly mempengharuhi growing economic regions are positive and significant in Profinsi Maluku and North Maluku.